Shifts in subsurface oxygen transport and consumption patterns in a restored coastal flood plain over five years - Emilio Grande; Ruby N. Ghosh; Charles McIntire; Michael J. Freeman; Peter Regier; Nicholas D. Ward (Limnology and Oceanography, 2026)
Groundwater dissolved oxygen (DO) variability in coastal systems remains poorly understood despite its importance for biogeochemical cycling and ecosystem modeling. This study investigates temporal variability in groundwater DO and its hydro‐climatic drivers across timescales (hourly to seasonal) in a coastal floodplain at Beaver Creek, Washington, USA, a site transitioning from a freshwater forest to brackish tidal wetland following restoration of tidal influence. Using 5 years of high‐frequency (5‐min) hydro‐meteorological and continuous groundwater DO data, we applied wavelet and information theory analyses to disentangle the role of different drivers (e.g., groundwater levels, temperature, precipitation, among others) on DO dynamics. Monitoring was initiated 5 years after the site was restored but prior to subsurface conditions reaching a new steady state. We found that DO pulses related to tidal flooding events were most frequent during earlier water years, dominated by hourly, daily and multiday variability. In later years both the frequency and magnitude of these DO pulses decreased, resulting in more prolonged subsurface anoxia. These shifts in DO patterns reflect gradually changing subsurface biogeochemical conditions as the system continues to fully transition from lowland forest to brackish wetland 10 years after restoration. This study highlights the critical role of timescale‐specific analyses in understanding wetland biogeochemistry by identifying dominant drivers of DO variability and linking them to ecosystem transitions. Our scale‐aware approach offers a framework for evaluating ecosystem responses to climate change, sea‐level rise, and restoration efforts in tidal wetlands.